A intermídialidade na obra de Coraline de Neil Gaiman e o filme Coraline e o Mundo Secreto dirigido por Henry Selick - Santos, Kelen Rodrigues Yamada dos (2018)
This research presents a reflexive explanation about the characteristics of the re-reading of a literary work for a cinematographic work, dialoguing with the intermidiality, exploring possibilities of the media transformation, beyond the simple compartivism between original work and derivative work, as objects of analysis were chosen the comic book Coraline Graphic Novel, adaptation and illustrations of Philip Craig Russell and the film Coraline and the Secret World (USA, 2009), animation in Stop Motion directed by Henry Selick. Through an exploratory bibliographical research, based on surveys of the literary and film work, the study sought to denote the understanding of the factors of art in the two language planes. Exploratory research requires sources of information, par excellence of written, electronic, and other documents (CERVO, et al., 2007). With the objective of analyzing the literary bases within each characteristic of the language, the comparative, sought to attribute the values of the work in both artistic media, graphic art and cinematographic art the same parameters, so as not to escape the original work. The present study will seek to address clearly and succinctly the importance of language and communication through media art, comics and cinema, its perspectives in relation to children, youth and adults, as well as to put the aspects of intermidiality, in the elaboration of the arts based on literary books.